Enhanced recovery after surgery on multiple clinical outcomes: Umbrella review of systematic reviews and meta-analyses. Issue 29 (17th July 2020) - Zhang, Xingxia; Yang, Jie; Chen, Xinrong; Du, Liang; Li, Ka; Zhou, Yong
Abstract: Background: Previously, many meta-analyses have reported the impact of enhanced recovery after surgery (ERAS) programs on many surgical specialties. Objectives: To systematically assess the effects of ERAS pathways on multiple clinical outcomes in surgery. Design: An umbrella review of meta-analyses. Date sources: PubMed, Embase, Web of Science and the Cochrane Library. Results: The umbrella review identified 23 meta-analyses of interventional study and observational study. Consistent and robust evidence shown that the ERAS programs can significantly reduce the length of hospital stay (MD: −2.349 days; 95%CI: −2.740 to −1.958) and costs (MD: −$639.064; 95%CI:: −933.850 to −344.278) in all the surgery patients included in the review compared with traditional perioperative care. The ERAS programs would not increase mortality in all surgeries and can even reduce 30-days mortality rate (OR: 0.40; 95%CI: 0.23 to 0.67) in orthopedic surgery. Meanwhile, it also would not increase morbidity except laparoscopic gastric cancer surgery (RR: 1.49; 95%CI: 1.04 to 2.13). Moreover, readmission rate was increased in open gastric cancer surgery (RR: 1.92; 95%CI: 1.00 to 3.67). Conclusion: The ERAS programs are considered to be safe and efficient in surgery patients. However, precaution is necessary for gastric cancer surgery. Abstract : Supplemental Digital Content is available in the text